PENGEMBANGAN KOMPETENSI PROFESIONAL GURU MELALUI PEMANFAATAN TIK UNTUK MENINGKATKAN PRESTASI AKADEMIK PESERTA DIDIK - Zulfiana Alia; Lilis Kholisoh Nuryani; Sumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of professional competence is carried out with the ultimate goal of education, building and strengthening the commitment, consistency and dedication of teachers to the development of the quality of education, one of which is marked by student learning outcomes. This type of research is a literature study (literature review), with stages, namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling a discussion, compiling conclusions based on the results of the analysis. The conclusion of this study is that the development of teacher professional competence through the use of ICT can improve learning outcomes in students. The essential aspects in the development of teacher professional competence through the use of ICT are facilities and infrastructure, teacher digital skills, teacher motivation and leadership, student involvement in learning. The role of the principal in the development of teacher professional competence through the use of ICT and the availability of facilities and infrastructure in schools.